1997
DOI: 10.1093/oxfordjournals.eurheartj.a015211
|View full text |Cite
|
Sign up to set email alerts
|

Atrial conduction abnormalities in patients with systemic progressive sclerosis

Abstract: Intra-atrial electromechanical coupling intervals were delayed in patients with progressive systemic sclerosis. Thus, the mechanical late diastolic filling time due to atrial contraction in the total diastolic phase was severely limited, and this resulted in a restricted mitral A wave. We should therefore evaluate patients with progressive systemic sclerosis for significant atrial abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…Atrial disruption caused by fibrosis has been suggested as the mechanism underlying IAB. Fibrosis was associated with both ischemic heart disease 29 and nonischemic heart disease, including systemic sclerosis, 29,30 dilated cardiomyopathy, 31 hypertrophic cardiomyopathy, 31 lymphoma, 32 and increased atrial strain because of valvular heart disease. 33 Histological studies demonstrated that right atrial tissue (including BB tissue) of patients with IAB shows apparent fibrosis, 34,35 though fibrosis of BB alone has not been described.…”
Section: Bb Blockmentioning
confidence: 99%
“…Atrial disruption caused by fibrosis has been suggested as the mechanism underlying IAB. Fibrosis was associated with both ischemic heart disease 29 and nonischemic heart disease, including systemic sclerosis, 29,30 dilated cardiomyopathy, 31 hypertrophic cardiomyopathy, 31 lymphoma, 32 and increased atrial strain because of valvular heart disease. 33 Histological studies demonstrated that right atrial tissue (including BB tissue) of patients with IAB shows apparent fibrosis, 34,35 though fibrosis of BB alone has not been described.…”
Section: Bb Blockmentioning
confidence: 99%
“…27) In our study of patients with PAF, the duration of PA-TMF was inversely correlated with LAA-FV, suggesting that PA-TMF reflects LA electrical and structural remodeling, resulting in prolonged inter-atrial conduction time, thereby enabling the estimation of LAA-FV in patients with PAF. The geometrical distance between the two atria may also be an important determining factor for inter-atrial conduction time.…”
Section: Discussionmentioning
confidence: 59%
“…26) Mizuno, et al previously reported that inter-atrial conduction time determined using TTE and ECG was delayed in patients with progressive systemic sclerosis. 27) They showed that the time interval between initiation of the P-wave and onset and the peak of the A-wave Each parameter was compared with LAA-FV using single regression analysis. A probability (P) value < 0.05 was considered statistically significant and marked by an asterisk.…”
Section: Discussionmentioning
confidence: 99%
“…This method can be used to predict paroxysmal AF. The distance between the two atria is a significant determinative factor for atrial conduction, and inter-nodal pathways may play a major role in inter-AEMD [20]. Previous studies demonstrated that AEMD durations were significantly prolonged in patients with paroxysmal AF [4,19].…”
Section: Discussionmentioning
confidence: 99%
“…The results of each question were totalled to measure generalised anxiety, with higher scores linked to greater anxiety (range 0-56). Anxiety severity was classified as mild (HAM-A: 0-17), mild to moderate (HAM-A: [18][19][20][21][22][23][24], and moderate to severe (HAM-A: 25-30).…”
Section: Study Populationmentioning
confidence: 99%